Traumatic inferior epigastric vessel haemorrhage - Dimassi, Hani (2015)
Inferior epigastric vessel (IEV) bleeding usually results in a localised rectus sheath haematoma. This condition was thought to be uncommon and sometimes overlooked or misdiagnosed. Lately the condition has become more prevalent with life threatening bleeding which may need emergency intervention to save life. A case report of IEV bleeding following trauma in a 17-year-old male is reported. A CT scan enabled localisation of the injury site and showed signs of active bleeding. Facilities for embolization didn't exist in the hospital at the time. The bleeding was life threatening which required an emergency laparotomy. The laparotomy confirmed the source of the bleeding as the left IEV. The offending vessel was ligated and the haematoma was evacuated. The patient recovered well and his life was saved. Bleeding from the IEV is thought to be rare and the result is usually a haematoma which can be treated conservatively. The presentation is changing and there is an increase in severity and frequency of the bleeding which can endanger life. If facilities for embolization do exist, a minimally invasive procedure is the method of choice. If on the other hand they don't exist, which is the case in many hospitals; laparotomy should be performed where there is a threat to life.